Recycled concrete aggregate mixed with crumb rubber under elevated temperature. (20th October 2019) - Saberian, Mohammad; Shi, Long; Sidiq, Amir; Li, Jie; Setunge, Sujeeva; Li, Chun-Qing
Highlights: Effect of elevated temperature on behaviours of RCA containing rubber was studied. The mixed samples were heated at different temperatures (20, 150, 300, 450, and 600 °C). X-ray micro-tomograph and unconfined compression strength tests have been performed. The samples collapsed at temperatures more than 500 °C. Abstract: The use of recycled concrete is a significant step to reduce the need for natural resources and the demand on landfill sites for disposing the waste. Previous studies have mainly focused on its behaviours under ambient temperature although the characteristics of recycled concrete after high temperature exposures is important in many practical applications such as fire resistance. Also, the effect of elevated temperature on the mechanical and porosity behaviours of recycled concrete aggregate (RCA) containing rubber for pavement base/subbase applications has never been studied. In this study, the effects of high-temperature environment on the mechanical properties of recycled concrete aggregate (RCA) mixed with crumb rubber (CR) in a range of 0.5–2% were investigated both experimentally and theoretically. Unconfined compression strength (UCS) and X-ray micro-tomograph tests were undertaken on the mixed samples which were heated to different temperatures ranging from 20 °C to 600 °C. It was observed from the experimental results that UCS increased under a higher temperature up to 300 °C. At an ambient temperature of 20 °C, RCA samples without any addition of CR exhibited the highest UCS value while under high temperature, RCA samples with 1% CR had the highest UCS value. The strength of RCA mixed with crumb rubber showed an increasing trend under a temperature higher than 150 °C, which can be attributed to the melting processes of the crumb rubber. According to the X-ray micro-tomograph tests, the inclusion of rubber led to a decreasing porosity. It is interesting to note that porosity rises when temperature increased from 20 °C to 150 °C. This may be due to the restructuring of the shape of rubber particles into spheres as well as the excessive pore water forces generated from water evaporation. Also, when the temperature increased from 150 °C to 450 °C, the porosity decreased since the melted rubber particles flowed into the voids and filled more pores. The outcomes of this study can provide practical guidance on the application of recycling concrete.